Disgrafia dalam Pembelajaran Menulis Narasi: Studi Literatur pada Peserta Didik SD Kelas Tinggi - Zuniar, Meutia; Iswara, Prana Dwija (YASIN, 2025)
Dysgraphia, as a specific writing disorder, constitutes a significant barrier to narrative writing instruction among upper-grade elementary school students. This study aimed to analyze the characteristics of dysgraphia, its impact on narrative writing ability, and effective instructional strategies based on a synthesis of recent literature. A systematic literature review method was employed by analyzing 15 SINTA-indexed articles published between 2020 and 2025. The findings reveal that dysgraphia has multidimensional characteristics covering physical–motor aspects (difficulties with fine motor coordination, illegible handwriting), linguistic aspects (systematic spelling errors, limited vocabulary), and cognitive aspects (limited working memory capacity, poor organization of ideas. The impact of dysgraphia on narrative writing ability is reflected in low technical quality of writing, incoherent narrative structure, and psychological consequences such as anxiety and avoidance of writing activities. Effective instructional strategies identified in the reviewed studies include multisensory approaches, curriculum modification through product differentiation, the use of assistive technology, and intensive collaboration among teachers, parents, and specialists. The study concludes that comprehensive understanding of the characteristics of dysgraphia and the implementation of integrated inclusive instructional strategies have the potential to significantly improve students’ narrative writing ability, while also underscoring the urgency of developing identification and intervention models for dysgraphia that are contextually aligned with instructional needs in Indonesia.